Rights and duties of the buyer under the sale of goods in Shari'ah and International trade law : a comparative analysis - Hassan, Mazin Abdulhameed Dawood (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
Sale of goods is considered as the most common kind of transaction in the world. The people practise sale of goods to satisfy their several, renewable, and daily needs. As a result, the buyer acquires some rights and bears some duties towards the seller. Basically, these rights and duties are provided by the applicable law in context which may or may not be the same as another. Thus, the purpose of this dissertation is, firstly, to discuss and compare the general concept of sale of goods in Shari'ah and international trade law. It also intends to examine the rights and the duties of the buyer under the sale of goods in Shari'ah and international trade law and, then, compare between the two laws in this regard. This research is based on library-based method where both sources of Shari'ah such as Qur'an and Hadith and sources of international trade law such as the United Nation Convention on Contracts for International Sale of Goods 1980 and the UNIDROIT Principles 2016 are taken into account. Upon comparing between the two laws as to the rights and duties of the buyer under the sale of goods, it becomes clear that there are, generally, significant similarities between the two laws. As for the rights of the buyer, there are some similarities and differences. The similarities include that the two laws recognise the right of negotiation and the right to receive the goods. The differences covers that Shari'ah recognize the right of examination of the goods before the conclusion of the contract but international trade law provides this right after it. As for duties of the buyer under the sale of goods, it seems that there are many similarities and few differences between the two laws. The similarities include that both of them impose the duty to pay the price and take the necessary steps to effect the payment. For the differences, Shari'ah, for example, does not acknowledge the duty to specify the form, the measurement or other features of the goods after the conclusion of the contract while international trade law does.